Goddess beyond boundaries: worshipping the Eternal Mother at a North American Hindu Temple - Pintchman, Tracy (Oxford scholarship online, 2024)
Tracy Pintchman sheds light on the spiritual creativity and religious life of the Parashakthi Temple in Pontiac, Michigan. Drawing on 15 years of field research, Pintchman reveals how Karumariamman, the goddess honoured by the temple, embodies the border-and-boundary-crossing dynamics of the lives of many of the congregants who worship at her temple, which in turn has become a site of religious innovation.